Nursing Care of The Case Invested in The Gynecology Clinic According to The Neuman Systems Model - Gonca Karatas Baran (Anadolu Hemşirelik ve Sağlık Bilimleri Dergisi, 2021)
Nursing theories and models are important for nursing practice and research. The Neuman Systems Model (NSM), guides nursing practice by providing a framework for collecting, analyzing individual service client system data and for planning, implementing and evaluating nursing care. It is a dynamic model with fixed elements. The purpose of this case report is to make a presentation of NSM used to care for a patient with gynecological disease and to create an example. In this study, three types of stressors (personal, interpersonal and environmental) and five major variable domains (physiological, psychological, sociocultural, spiritual and developmental) of the case were defined. The personal basic structure of the case was defined and the stressors that had permanent and temporary effects on the individual were determined. It has been determined that the case needs information about the disease and treatment process, has anxiety about uncertainty, and is affected by the difficulties of the pandemic process. The detected nursing diagnoses, the nursing goals and practices for these diagnoses were determined, and then the nursing results were evaluated. The NSM model can be recommended to nurses so that they can provide care by being aware of the physiological, psychological and social needs of the patients throughout the whole process.